Doctors of deception : what they don't want you to know about shock treatment - Andre, Linda, 1959- (Rutgers University Press, 2009)
Mechanisms and standards exist to safeguard the health and welfare of the patient, but for electroconvulsive therapy (ECT)used to treat depression and other mental illnessessuch approval methods have failed. Prescribed to thousands over the years, public relations as opposed to medical trials have paved the way for this popular yet dangerous and controversial treatment option. Doctors of Deception is a revealing history of ECT (or shock therapy) in the United States, told here for the first time. Through the examination of court records, medical data, FDA reports, industry claims, her own ex.